2006
DOI: 10.1146/annurev.physiol.68.072304.113102
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Effects of Mechanical Force on Airways

Abstract: Airways are embedded in the mechanically dynamic environment of the lung. In utero, this mechanical environment is defined largely by fluid secretion into the developing airway lumen. Clinical, whole lung, and cellular studies demonstrate pivotal roles for mechanical distention in airway morphogenesis and cellular behavior during lung development. In the adult lung, the mechanical environment is defined by a dynamic balance of surface, tissue, and muscle forces. Diseases of the airways modulate both the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
94
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(97 citation statements)
references
References 138 publications
(133 reference statements)
1
94
1
1
Order By: Relevance
“…However, tiotropium has no effect on inflammatory markers in sputum (IL-6, CXCL8 and myeloperoxidase) or in the circulation (IL-6 and CRP) of COPD patients, despite a reduction in exacerbations [170]. Anticholinergics (and other bronchodilators) may reduce the mechanical forces in the lung due to airway closure and this might reduce the expression of TGF-b and other mediators released in response to the mechanical strain of epithelial cells [171,172]. This may have beneficial effects on systemic inflammation.…”
Section: -4xmentioning
confidence: 99%
“…However, tiotropium has no effect on inflammatory markers in sputum (IL-6, CXCL8 and myeloperoxidase) or in the circulation (IL-6 and CRP) of COPD patients, despite a reduction in exacerbations [170]. Anticholinergics (and other bronchodilators) may reduce the mechanical forces in the lung due to airway closure and this might reduce the expression of TGF-b and other mediators released in response to the mechanical strain of epithelial cells [171,172]. This may have beneficial effects on systemic inflammation.…”
Section: -4xmentioning
confidence: 99%
“…As a consequence of its effect on airway calibre and ASM length, lung volume as a determinant of lung function has recently received more attention [30,196]. MCCLEAN et al [13] produced a chronic decrease in lung volume (25% below FRC) in sheep by restricting their chests with a corset, and examined the subsequent in vitro contractility of ASM from these animals after 4 weeks.…”
Section: Effects Of Chronic Lung-volume Alteration and Smooth Muscle mentioning
confidence: 99%
“…In actual bronchi, cilia sweep upward to remove debris from the lungs, but since our model was symmetric in the x and y directions (without strain) we did not expect an overall directionality. The effects of dynamic strain on ciliary motion were not considered in this work, although it has been previously shown that mechanical stimulation leads to intra-and intercellular Ca 2Ï© signaling that would increase ciliary beat frequency (5,56,66). Therefore, the increase in overall infection rate that we see is unlikely to be due to any changes in ciliary beat frequency or coordination.…”
Section: Discussionmentioning
confidence: 93%
“…In particular, several different in vitro models of the bronchial airway wall have been used to demonstrate that mechanical stress, at levels relevant to bronchoconstriction, can itself induce changes in gene and protein expression in epithelial cells and fibroblasts that are consistent with airway wall remodeling events, as well as matrix remodeling and smooth muscle cell (SMC) migration and proliferation (11,12,31,42,60,66,73).…”
mentioning
confidence: 99%